A Study of Sugarcane Waste for Biomass Energy in the Supply of Electrical Energy - Ramadoni Syahputra; Oki Iwan Pambudi; Faaris Mujaahid; Indah Soesanti (Journal of Electrical Technology UMY, 2020)
This paper presents a study of sugarcane waste for biomass energy in the supply of electrical energy. Biomass is a renewable energy source derived from organic matter such as wood and sugarcane waste. As much as 30 per cent of sugar cane raw material for sugar production is in the form of sugar cane waste. This sugarcane waste is very potential to be developed as a biomass energy raw material. In this study, an analysis of the potential of sugarcane waste at the Madukismo Yogyakarta sugar mill was carried out. Observations made to record how much cane waste is produced by the sugar factory every day of the year. Furthermore, these data are analyzed using Homer Energy software to obtain the potential of electrical energy produced during a year. The analysis was also carried out on the amount of electricity demand in the sugar factory. This study is done to calculate how much the contribution of electrical energy from biomass as a provider of electricity supply. The results of the analysis showed that sugarcane waste as much as 1.035 tons/day on average was able to meet all the electrical energy requirements for the operation of the Madukismo sugar factory.